2020
DOI: 10.1245/s10434-020-08649-6
|View full text |Cite
|
Sign up to set email alerts
|

The Peritoneal Cancer Index is a Strong Predictor of Incomplete Cytoreductive Surgery in Ovarian Cancer

Abstract: Background Extent of tumor load is an important factor in the selection of ovarian cancer patients for cytoreductive surgery (CRS). The Peritoneal Cancer Index (PCI) gives exact information on tumor load but still is not standard in ovarian cancer surgery. The aim of this study was to find a PCI cutoff for incomplete CRS. The secondary aims were to identify reasons for open-close surgery and to compare surgical complications in relation to tumor burden. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 31 publications
1
33
0
Order By: Relevance
“…In their study 62% of patients with PCI above 24 had an unsatisfactory surgical outcome de ned as SCS. The authors conclude that neoadjuvant chemotherapy could be considered if the PCI is higher than 24 .Theis study just emphasizes the reasons underlying SCS but has no predictive value for SCS or open-close surgery [16].…”
Section: Discussionmentioning
confidence: 94%
“…In their study 62% of patients with PCI above 24 had an unsatisfactory surgical outcome de ned as SCS. The authors conclude that neoadjuvant chemotherapy could be considered if the PCI is higher than 24 .Theis study just emphasizes the reasons underlying SCS but has no predictive value for SCS or open-close surgery [16].…”
Section: Discussionmentioning
confidence: 94%
“…However, a risk for disease upstaging as well as a documented risk of the abdominal wall metastasis and necessity for abdominal wall resection are arguments against laparoscopic evaluation of PCI [18,19]. We previously found that PCI evaluation is useful for assessment of operability and we identified a cut-off of !24 in relation with the risk for incomplete cytoreduction [13]. Additionally, pre-operative cancer antigen-125 > 600 U/mL, PCI >20 and intra-operative mapping of ovarian cancer score >6 are reported to be predictors of complete tumour resection, while the combination of all these three values predicted the incomplete resection of disease in up to 90% of patients [20].…”
Section: Discussionmentioning
confidence: 97%
“…PCI is widely used during the evaluation of the extent of colorectal carcinosis and prediction of surgical complexity [12]. Elevated PCI has been associated with higher FIGO stage, prolonged duration of surgery, an increased number of visceral resections, incomplete cytoreduction and postoperative complications [13,14]. PCI scoring is, however, to a lesser extent used by ovarian cancer surgeons and it is not fully known which baseline variables are the most important predictors for high-grade postoperative complications.…”
Section: Introductionmentioning
confidence: 99%
“…The burden of peritoneal carcinomatosis determined by the PCI score [18] and the extent of cytoreduction achieved significantly influence the survival rates. Some studies have used PCI scores in identifying patients with limited peritoneal cancer indicating that those with a lesser PCI score could benefit more with the combined approach.…”
Section: Discussionmentioning
confidence: 99%